Storage of corn seeds infested by weevil - Costa, Leidiane De Oliveira; Marques, Sheury Celante [UNESP]; Pereira, Rosane Rodrigues Da Costa; Pereira, Carlos Eduardo (Instituto Biológico, 2021)
Weevil is one of the main pests of stored corn. The adults feed on intact and broken seeds or bran, while the larvae develop by feeding on the inside of the seeds, resulting in a reduction in weight and physiological quality. The objective of this study was to evaluate the effects of Sitophilus zeamais infestation on corn seeds during storage. Corn seeds were infested using insect densities: 0, 36, 72, 108, and 144 individuals per 240 g of seeds. The infested seeds were placed in individualized plastic containers and covered with voile fabric. The seeds were stored for 60 days under laboratory conditions with an average temperature of around 27 °C and relative humidity of 85%. Initially and every 15 days of storage for 60 days, the seeds were evaluated using the parameters: number of S. zeamais individuals, total number of infested seeds, seed weight loss, germination test and seedling emergence in the tray. The population increase of S. zeamais causes a decrease on the physical and physiological quality of stored corn seeds, but the deterioration rate does not increase in the same proportion as the weevil population growth rate.
Keywords: germination; physical damage; Zea mays; Sitophilus zeamais